Building brand identity through social media platform during Covid-19 pandemic / Mohd Remie Mohd Johan, Md. Azalanshah Md. Syed and Hamedi Mohd Adnan - Mohd Johan, Mohd Remie; Md. Syed, Md. Azalanshah; Mohd Adnan, Hamedi (Universiti Teknologi MARA, Perlis, 2022)
Building a substantial brand identity value has become a key issue for many companies’ reputations. In previous years, the majority of studies focused on the consumer’s perspective on organizations’ brand equity value. Thus, this study expanded on earlier research by offering a more in-depth exploration and understanding of organizations’ perspectives on how they develop their brand identity through social media platforms. A qualitative approach using semi-structured interviews was employed to explore the small-medium enterprise (SME) of the food and beverage service industry. Interviews were conducted with independent food truck businesses in Kuala Lumpur, Malaysia. This study yielded results that showed respondents’ interest in brand identity building on social media platforms. Creating a brand identity perception that is recognized by its customers through social media has become an essential activity for food truck (FT) owners to communicate their brand digitally.